Soybean response to fertilization and potassium availability in Latossolo Roxo álico (Oxisol) - Borkert, Clóvis Manuel; Farias, José Renato Bouças; Sfredo, Gedi Jorge; Tutida, Fábio; Spoladori, Cláudio Luís (Pesquisa Agropecuaria Brasileira, 1997)
Double-cropping soybean-wheat has been cultivated in the Latossolo Roxo álico (Haplorthox) soils of Paraná State, Brazil, since the 70's. Due to credit restrictions to agriculture, since then most farmers have not used fertilizers for soybean or applied less potassium than that removed by the seeds. This system leads to low soil fertility and as a consequence low yields. With the objective to study the best technology for potassium fertilization and its residual effects on the soybean, a long term experiment was run in a Latossolo Roxo álico soil, in Campo Mourão County. In the first five growing seasons, 1983/84 to 1987/88, it was applied, once a year, the doses of zero, 40, 80, 120, 160 and 200 kg/ha of K2O/ha in the sowing row and broadcasted. In the next five growing seasons, soybean was cultivated on the residual effect of the potassium fertilization and also it was studied its effects on K-plant tissue and soybean yield. It was concluded that Latossolo Roxo álico can not be cultivated for more than one year with the double-cropping soybean-wheat system without replace the K-removed by the seed.